Analýza oxidačního poškození explantovaných komponent náhrady kyčelního kloubu Beznoska/Poldi - Fulín, Petr; Pokorný, David; Šlouf, Miroslav; Nevoralová, Martina; Vacková, Taťana; Dybal, Jiří; Kaspříková, Nikola; Landor, Ivan (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2016)
UNLABELLED: PURPOSE OF THE STUDY Ultrahigh molecular weight polyethylene (UHMWPE) is today the most frequently used bearing surface in total joint replacements (TJR) because of its properties, i.e., excellent biocompatibility, good mechanical and tribological performance and high wear resistance. UHMWPE liners are the most loaded TJR components and, therefore, their properties are decisive for TJR longevity. This study had three objectives: 1) to evaluate the oxidative degradation of explanted UHMWPE components; 2) to look for a statistically significant relationship between the extent of oxidative degradation and the durability of joint replacements; and 3) to investigate whether the durability of a TJR was related to the type of sterilisation used in manufacture. MATERIAL AND METHODS The study included 26 acetabular components obtained at revision arthroplasty between 2004 and 2013 from patients in whom a Beznoska/Poldi total hip replacement was used in the period from 1977 to 2002. The average age of the patients at the time of primary implantation was 57.9 years, the average longevity of the components removed was 18.63 years (range, 6.9 to 27.9 years). Samples of worn out and unworn areas from explanted components were processed in a three-step procedure in order to finally obtain 2-mm microtome sections. These were studied by infrared microspectroscopy. Oxidative damage to UHMWPE was determined as the oxidation index (OI); radiation damage to UHMWPE during sterilization was evaluated as the transvinylene index (VI); oxidation-induced changes in the polymer structure and its properties were characterised as the crystallinity index (CI); and local changes in mechanical properties due to oxidative degradation were assessed as microhardness (MH). Spearman's correlation coefficient and the Wilcoxon two-sample test were used for statistical analysis. RESULTS The OI values (average and maximum) in both worn out and unworn surface areas were related to component longevity. The difference between the oxidation index of ruptured components and that of the other components was statistically significant. Significant differences were also found between the average and maximum OI values of worn out areas and those of unworn surfaces. The relationship between the average oxidation index in both the unworn and worn out areas of UHMWPE components and the longevity of cracked components was statistically significant. DISCUSSION Our results show that the OI values obtained by microspectroscopy correlated with both the microscopic damage and the longevity of UHMWPE liners and the correlation was statistically significant also in relation to the longevity of total replacements. Relationships amongst OI, VI, CI and MH values as well as their relation to failure and longevity of total replacements are discussed. CONCLUSIONS It can be concluded that infrared microspectroscopic measurement of OI values is a simple and fast method to characterise UHMWPE liners. In addition, the IR spectra also show other supplementary characteristics, such as VI and CI indices. These values provide information on the quality of various UHMWPE types currently used in TJR surgery. The types of UHMWPE which exhibit high oxidative degradation should be avoided in clinical practice due to increased risk of early TJR failure. Responsible orthopedic surgeons should be aware of this fact and, if possible, collaborate with an independent, noncommercial laboratory in order to evaluate the quality of various UHMWPE liners used in their hospitals. KEY WORDS: UHMWPE, oxidation, total joint replacement, infrared spectroscopy, microhardness.
Keywords: oxidační stres; biokompatibilní materiály; Oxidative Stress; lidé; Reoperation; Spectrophotometry, Infrared; Polyethylenes; reoperace; Biocompatible Materials; Materials Testing; selhání protézy; Aged; spektrofotometrie infračervená; testování materiálů; náhrada kyčelního kloubu; lidé středního věku; Arthroplasty, Replacement, Hip; senioři; Middle Aged; polyethyleny; Prosthesis Failure; Humans